2021
DOI: 10.1155/2021/6471400
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Jinchan Oral Liquid in the Treatment of Children with Respiratory Syncytial Virus Pneumonia Based on Network Pharmacology and Molecular Docking Technology

Abstract: Objective. Exploration of the underlying molecular mechanism of Jinchan Oral Liquid (JOL) in treating children with the respiratory syncytial virus (RSV) pneumonia to provide new evidence for the clinical application. Methods. The active components and target genes of JOL were screened by the TCMSP database. The targets of RSV pneumonia were obtained from the GeneCards, OMIM, DrugBank, and PharmGKB database. Then, we constructed the active component-target network and screened the core genes. The overlaps were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The detection rate of RSV in children with wheezing illnesses in Suzhou, China, was 22% and reached 42.4% at the peak of the RSV epidemic [ 32 ]. Another study found that RSV accounted for 67.4% of the detected viruses in children with wheezing illness, ranking first among the detected pathogens [ 33 ]. RSV infection was also associated with recurrent wheezing after infant bronchiolitis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate of RSV in children with wheezing illnesses in Suzhou, China, was 22% and reached 42.4% at the peak of the RSV epidemic [ 32 ]. Another study found that RSV accounted for 67.4% of the detected viruses in children with wheezing illness, ranking first among the detected pathogens [ 33 ]. RSV infection was also associated with recurrent wheezing after infant bronchiolitis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Prathap et al revealed that stachydrine, a pyrrolidine betaine, binds IL-6 and inhibits it, with a binding energy of −5.9 kcal/mol and hydrogen bonding with GLU: 42 [ 77 ]. Docking another phytocompound, the flavonoid quercetin, with IL-8 a binding energy of −7.9 kcal/mol was reported [ 78 ]. The docking energy score of stachydrine with TNF-α is −6.8 and hydrogen bonding with ARG: 332, ARG: 372 and VAL: 373 was observed [ 77 ].…”
Section: Discussionmentioning
confidence: 99%